A274 THE EFFECT OF PRUCALOPRIDE ON SMALL BOWEL TRANSIT TIME FOR INPATIENTS UNDERGOING SMALL BOWEL CAPSULE ENDOSCOPY - Alsahafi, M A (J Can Assoc Gastroenterol, 2018)
BACKGROUND: Inpatient small bowel capsule endoscopy (SBCE) has been associated with a decrease in the completion rate compared to outpatient SBCE. However delaying the performance of SBCE until hospital discharge may result in a decrease in the diagnostic yield. Therefore, interventions to shorten small bowel transit time are needed to increase the completion rates. Prucalopride is 5-HT4 receptor agonist that has been shown to decrease the whole gut transit time. AIMS: To investigate the effect of prucalopride on small bowel transit time for hospitalized patients undergoing SBCE. METHODS: This was a retrospective study that included all hospitalized patients who underwent SBCE between November 2011 and September 2016 at Vancouver General Hospital. In the period between March 2014 and December 2015, all patients received prucalopride at the time of capsule ingestion. Prucalopride was not given outside of this period. SBCE studies were excluded if the capsule was retained, other prokinetic agents were given, technical failure, endoscopic placement or if patients had prior small bowel resection. RESULTS: A total of 66 SBCE were performed. 12 SBCE were excluded. For the 54 included studies, the mean age for patients was 64 years. 64% of SBCE were done in male patients. The indications were obscure gastrointestinal bleeding in 51 and abnormal radiology in 3 patients. 29 patients received prucalopride. The overall completion rate was 85% and the mean small bowel transit time was 186 minutes. The prucalopride group had a significantly shorter small bowel transit time (132 vs. 277, p<0.001), and higher diagnostic yield (75% vs. 44%, p= 0.03) compared to the non prucalopride group. There was a trend for higher completion rate in the prucalopride group (93% vs. 76%, p= 0.16). CONCLUSIONS: Our results suggest that prucalopride is an effective intervention to shorten small bowel transit time, increase the diagnostic yield and potentially increases the completion rate. FUNDING AGENCIES: None